GERM-21. PRELIMINARY RESULTS OF RESPONSE ASSESSMENT WITH 18F-FET PET FOR INTRACRANIAL GERM CELL TUMORS IN ADOLESCENTS. Issue 2 (22nd June 2018) - Marner, Lisbeth; Nysom, Karsten; Sehested, Astrid; Borgwardt, Lise; Mathiasen, René; Wehner, Peder Skov; Henriksen, Otto Mølby; Lundemann, Michael; Thomsen, Carsten; Bøgeskov, Lars; Skjøth-Rasmussen, Jane; Broholm, Helle; et al.
Abstract: BACKGROUND: Intracranial germinoma (WHO grade IV) has a good prognosis as over 90% can be cured with chemo- and radiotherapy, while intracranial nongerminomatous germ cell tumors (NGGCT) also have a good although somewhat less favorable outcome. We evaluated the use of 18 F-fluoro-ethyltyrosine ( 18 F-FET) positron emission tomography (PET) for response assessment in intracranial germinoma and NGGCT. METHODS: Six patients (5 males, age 13-17 years) diagnosed with intracranial germinoma (n=4) or NGGCT (elevated alpha-fetoprotein (AFP)) (n=2) were included and 18 F-FET PET scans were performed at baseline and after 9-12 weeks of chemotherapy (treated according to SIOP CNS GCT 2). One germinoma patient declined follow-up 18 F-FET PET. RESULTS: All germinoma and one NGGCT patients had partial or complete response on MRI and were subsequently treated with proton radiation therapy, and are in clinical complete response (cCR). The second NGGCT patient had normalisation of AFP but progression on MRI; he was subsequently operated where histology showed only residual teratoma. He received further chemo- and radiotherapy and is in cCR. All patients with follow-up PET showed marked decrease of 18 F-FET activity uptake after chemotherapy. Maximal tumor-to-background ratio decreased from 2.2 ± 0.4 before chemotherapy to 1.4 ± 0.3, p=0.001 (paired t-test). CONCLUSIONS: In five patients treated successfully for intracranial germ cell tumors, 18 F-FET PET showed a marked decrease in activity uptake in response to chemotherapy. The results are promising for further studies of the use of 18 F-FET PET in response assessment in this disease, possibly to assist radiation therapy dosing with the aim to reduce late effects.